Visual snow: A systematic review and a case series. (November 2022) - Sampatakakis, Stefanos N; Lymperopoulos, Loukas; Mavridis, Theodoros; Karagiorgis, Georgios; Papadopoulos, Constantinos; Deligianni, Christina I; Mitsikostas, Dimos D
Background: Visual Snow Syndrome is a recently recognized neurological condition presenting, continuous, tiny dots across the entire visual field, accompanied by nyctalopia, photophobia and palinopsia that persist for months. It may be part of migraine aura spectrum, yet its definition is still questionable. Diagnostic criteria for Visual Snow Syndrome are included in the supplemental material of ICHD-3. We aimed to summarize recent data to improve the understanding of Visual Snow Syndrome. Methods: After presenting four new cases, we conducted a PRISMA systematic search in PubMed/MEDLINE and Embase databases using the keyword "visual snow" with specific inclusion and exclusion criteria. Results: From the 855 articles identified 30 were included for the qualitative analysis. These reports covered five aspects related to Visual Snow Syndrome: epidemiology, clinical features, comorbidities, pathophysiology, and treatment. We found limited data concerning Visual Snow Syndrome's epidemiology (one study). Clinical presentation (22 articles) and the comorbidities (migraine with aura and tinnitus most often, five reports) are described in detail. The pathophysiology of Visual Snow Syndrome is only approached with hypotheses, but several neuroimaging studies have been identified (seven articles). Treatment is based on single case reports only. Conclusion: Data for Visual Snow Syndrome are few and not strong enough to support Visual Snow Syndrome as a medical identity. Further investigation is needed.